Plastic master batch based on recycled pet material and preparation method thereof

By blending the pretreated PET recycled material with modified lignin, multi-effect antibacterial agent, etc. under high temperature and high pressure conditions, the obtained plastic masterbatch has excellent mechanical properties, efficient antibacterial properties and flame retardant properties, solving the problem of insufficient application of existing recycled PET materials in the field of high-performance plastics, and realizing resource reuse and environmentally friendly high-performance plastic products.

CN119529491AInactive Publication Date: 2025-02-28JIANGXI LICHENG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722702.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing recycling PET materials are rarely used in the field of high-performance plastics, and have low viscosity and poor mechanical strength. They are prone to breed harmful bacteria under certain temperature and humidity conditions, affecting human health.

Method used

Plastic masterbatches based on recovered PET material are prepared by mixing the pretreated PET recycled material, modified lignin, multi-effect antibacterial agent, antioxidant and lubricant in a mixer and melt blended in a twin-screw extruder.

Benefits of technology

Reuse of resources is realized, pollution is reduced, and environmentally friendly; through pretreatment and the use of modified lignin, the mechanical properties, antibacterial properties and flame retardant properties of the masterbatch are enhanced; the synergistic effect of multi-effect antibacterial agents further improves the antibacterial and flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158445230000031
    Figure BDA0005158445230000031
  • Figure BDA0005158445230000041
    Figure BDA0005158445230000041
  • Figure BDA0005158445230000042
    Figure BDA0005158445230000042
Patent Text Reader

Abstract

The invention discloses a plastic master batch based on a recycled pet material and a preparation method of the plastic master batch, and belongs to the technical field of plastic recycling. Comprising the following raw materials in parts by weight: 80-100 parts of a pretreated PET reclaimed material, 10-20 parts of modified lignin, 6-18 parts of a multi-effect antibacterial agent, 4-8 parts of an antioxidant and 3-5 parts of a lubricant. The prepared master batch takes the PET recycled material as a raw material, so that the recycling of resources is realized, and the master batch is environment-friendly; wherein the modified lignin is good in compatibility with a PET matrix, so that the mechanical property, the antibacterial property and the flame retardant property of the master batch are enhanced to a certain extent; wherein the multi-effect antibacterial agent and the modified lignin have a synergistic effect, so that the flame retardant property and the antibacterial property of the master batch are greatly enhanced; therefore, the master batch prepared by the preparation method disclosed by the invention is excellent in mechanical property, also has efficient antibacterial property and flame retardant property, is environment-friendly, realizes reutilization of resources, and has an important application value in the technical field of plastic recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic recycling, and in particular, relates to a plastic masterbatch based on recycled PET materials and a preparation method thereof. Background Art

[0002] With the rapid development of the plastics industry, plastic products have been widely used in various industries. Among them, polyethylene terephthalate (PET) has good transparency and glossiness, making it an ideal choice for manufacturing various transparent packaging materials. It is produced and used in large quantities in fiber, film, resin and other materials related to life, as well as in the food field such as drinking water and carbonated beverage bottles. However, the large-scale production and use is accompanied by an increase in plastic waste. Due to the non-degradability of PET, it has caused serious white pollution over time and damaged the earth's ecological environment. Therefore, the recycling of waste PET is becoming more and more important.

[0003] At present, recycled PET materials are mainly used for fibers, sheets, non-food packaging bottles, and a small amount of plastic steel belts and monofilaments. They are rarely used in the field of high-performance plastics, which is a big gap in the market. However, the viscosity of recycled PET materials is low and the mechanical strength is poor, which makes it difficult to meet the requirements of high-performance plastics. Moreover, under certain temperature and humidity conditions, the surface of recycled PET materials is prone to breeding harmful bacteria and other microorganisms, which affects human health. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of plastic recycling technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a plastic masterbatch based on recycled PET material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing plastic masterbatch based on recycled PET materials, comprising the following steps:

[0007] The pretreated PET recycled material, modified lignin, multi-effect antibacterial agent, antioxidant and lubricant are stirred and mixed evenly in a mixer, and then put into a twin-screw extruder for melt blending, extrusion and granulation to obtain a plastic masterbatch based on recycled PET material.

[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of pretreated PET recycled material, 10-20 parts of modified lignin, 6-18 parts of multi-effect antibacterial agent, 4-8 parts of antioxidant, and 3-5 parts of lubricant.

[0009] Furthermore, the antioxidant is a hindered phenol antioxidant.

[0010] Furthermore, the lubricant is one of stearic acid, zinc stearate and magnesium stearate.

[0011] Furthermore, the pretreated PET recycled material is prepared by the following steps:

[0012] The PET recycled material was added to a pulverizer and crushed, then added to water, stirred for 5 minutes, and then sodium dodecylbenzene sulfonate was added. The stirring was continued for 25 minutes, filtered, washed with water for 3-4 times, dried in an oven at 100°C for 2 hours, and then added to tetrahydrofuran. After stirring for 30 minutes, filtered, the filter cake was washed with ethanol solution, and dried in an oven at 100°C for 1 hour to obtain the pretreated PET recycled material.

[0013] Furthermore, the ratio of the amount of the PET recycled material, water, sodium dodecyl sulfate and tetrahydrofuran is 1 g:40 mL:3.1 g:20 mL.

[0014] By crushing and washing the recycled PET materials, impurities in the recycled PET materials can be effectively removed.

[0015] Furthermore, the modified lignin is prepared by the following steps:

[0016] Add lignin to ethanol aqueous solution, disperse it evenly by ultrasonication, then add silane coupling agent KH-550, control the reaction temperature to 85°C, keep the reaction for 5 hours, stir continuously during the reaction, filter, wash with anhydrous ethanol 2-3 times, and vacuum dry for 2 hours to obtain modified lignin.

[0017] Furthermore, the usage ratio of the lignin, the ethanol aqueous solution, and the silane coupling agent KH-550 is 1 g:100 mL:4.6 g.

[0018] Lignin is abundant in source, environmentally friendly and renewable, and has certain antibacterial and flame retardant properties. Lignin is modified by silane coupling agent KH-550, that is, an organic layer is formed on its surface, which reduces the polarity of lignin and improves the interface compatibility between lignin and PET matrix, so that its performance can be fully exerted. It can be used as a reinforcing material to enhance the mechanical properties of plastic masterbatch and a certain degree of antibacterial and flame retardant properties.

[0019] Furthermore, the multi-effect antibacterial agent is prepared by the following steps:

[0020] S1. At room temperature, under nitrogen protection, isocyanuric acid was dissolved in deionized water in a three-necked flask equipped with a stirring device, sodium hydroxide was added after stirring, and 4-chloro-1-butanol was slowly added dropwise to the three-necked flask. Under magnetic stirring, the reaction was fully reacted at room temperature for 8 hours. After the reaction was completed, the pH was adjusted to 6-7 with dilute sulfuric acid, and the solvent was removed with a rotary evaporator, and then washed with anhydrous ethanol 3-4 times, and vacuum dried to obtain intermediate 1; the ratio of isocyanuric acid, deionized water, sodium hydroxide, and 4-chloro-1-butanol was 14.7g:100mL:7.9g:10.8g;

[0021] Isocyanuric acid reacts with 5-chlorovaleraldehyde, and the intermediate 1 is obtained by controlling the molar ratio of the two to be close to 1:1 and the isocyanuric acid to be slightly excessive. The specific reaction process is as follows:

[0022]

[0023] S2. At room temperature and under nitrogen protection, phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile were uniformly mixed in a three-necked flask equipped with a stirring reflux device, the reaction temperature was controlled to 65°C, the reaction was stirred for 6 hours, and then the temperature was raised to 120°C, and the reflux reaction was carried out until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, the solvent was removed by distillation under reduced pressure, and the mixture was washed with dichloromethane 3-4 times and dried in vacuo to obtain intermediate 2; the ratio of phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile was 34.3g:13.6g:100mL;

[0024] Phosphorus oxychloride and pentaerythritol react, and the molar ratio of the two is controlled to be close to 2:1, and the phosphorus oxychloride is excessive to obtain intermediate 2; the specific reaction process is as follows:

[0025]

[0026] S3, in a three-necked flask equipped with a stirring device, the intermediate 1, the intermediate 2, triethylamine and toluene were mixed and stirred uniformly, heated to 75 ° C, and kept warm for 3 hours. After the reaction was completed, the triethylamine hydrochloride was filtered out, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two was 3:1), the eluent was removed by rotary evaporation, and vacuum dried to obtain intermediate 3; the ratio of the amount of intermediate 1, intermediate 2, triethylamine, and toluene was 42.2g:29.5g:30mL:150mL;

[0027] Triethylamine is used as an acid-binding agent to remove the hydrogen chloride generated by the reaction, accelerating the reaction. Intermediate 1 and intermediate 2 undergo a nucleophilic substitution reaction. By controlling the molar ratio of the two to be close to 2:1 and intermediate 1 to be slightly excessive, two -Cl groups on intermediate 2 participate in the reaction to obtain intermediate 3. The specific reaction process is shown below:

[0028]

[0029] S4. In a three-necked flask equipped with a stirring device, the intermediate 3 and acetone were mixed, and magnetic stirring was performed for 2 hours. After uniform dispersion, sodium hypochlorite was added, and the mixture was reacted at room temperature for 6 hours under light-proof conditions. After the reaction was completed, the solvent was removed by vacuum distillation, and the mixture was dried in vacuo to obtain a multi-effect antibacterial agent; the ratio of the intermediate 3, acetone, and sodium hypochlorite was 62.6 g: 200 mL: 29.6;

[0030] Under the action of sodium hypochlorite, the NH bond in the intermediate 3 molecule is converted into an N-Cl bond to obtain a multi-effect antibacterial agent; the structure of the multi-effect antibacterial agent is shown below:

[0031]

[0032] The prepared multi-effect antimicrobial agent molecule is centered on a spirocyclic phosphate and is connected to two cyclic halogenamine structures, wherein the spirocyclic phosphate has a good flame retardant effect and a stable six-membered heterocyclic structure. During combustion, the pentaerythritol skeleton forms a char protective layer to inhibit further combustion of the PET matrix, and can synergize with the N element and lignin in the multi-effect antimicrobial agent molecule to greatly enhance the flame retardant properties of the matrix. In addition, the two cyclic halogenamine structures introduce a large number of active chlorine atoms, have broad-spectrum and high-efficiency antimicrobial properties, and are less likely to cause microorganisms to develop drug resistance than other types of antimicrobial agents, have good stability, regeneration and durability, can synergize with lignin to greatly enhance the antimicrobial properties of the matrix.

[0033] Beneficial effects of the present invention:

[0034] 1. The masterbatch prepared by the present invention uses PET recycled material as raw material, realizes resource recycling, reduces pollution, and is environmentally friendly;

[0035] 2. By pre-treating the PET recycled materials, some impurities in the PET recycled materials are removed, making the raw materials purer;

[0036] 3. By modifying lignin, the compatibility with the PET matrix is ​​improved, and the mechanical properties of the masterbatch and the antibacterial and flame retardant properties to a certain extent are enhanced;

[0037] 4. The prepared multi-effect antibacterial agent can work synergistically with the modified lignin, greatly enhancing the flame retardant and antibacterial properties of the masterbatch;

[0038] Therefore, the masterbatch prepared by the present invention has excellent mechanical properties, high-efficiency antibacterial and flame-retardant properties, and is environmentally friendly, thus realizing resource recycling and having important application value in the field of plastic recycling technology. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Embodiment 1

[0041] Preparation of multi-effect antibacterial agent:

[0042] S1. At room temperature, under nitrogen protection, 14.7 g of isocyanuric acid was dissolved in 100 mL of deionized water in a three-necked flask equipped with a stirring device. After stirring evenly, 7.9 g of sodium hydroxide was added, and then 10.8 g of 4-chloro-1-butanol was slowly added dropwise to the three-necked flask. Under the action of magnetic stirring, the reaction was fully reacted at room temperature for 8 h. After the reaction was completed, the pH was adjusted to 6-7 with dilute sulfuric acid (mass fraction 12%), and the solvent was removed with a rotary evaporator, and then washed with anhydrous ethanol 3-4 times, and vacuum dried to obtain intermediate 1;

[0043] S2. At room temperature and under nitrogen protection, 34.3 g of phosphorus oxychloride, 13.6 g of pentaerythritol and 100 mL of anhydrous acetonitrile were mixed evenly in a three-necked flask equipped with a stirring reflux device, the reaction temperature was controlled to 65°C, the reaction was stirred for 6 hours, and then the temperature was raised to 120°C, and the reflux reaction was carried out until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, the solvent was distilled off under reduced pressure, and the mixture was washed with dichloromethane 3-4 times and dried in vacuo to obtain intermediate 2;

[0044] S3, in a three-necked flask equipped with a stirring device, 42.2g of intermediate 1, 29.5g of intermediate 2, 30mL of triethylamine and 150mL of toluene were mixed and stirred evenly, heated to 75°C, and kept warm for 3h. After the reaction was completed, triethylamine hydrochloride was filtered out, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two was 3:1), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 3;

[0045] S4. In a three-necked flask equipped with a stirring device, 62.6 g of intermediate 3 was mixed with 200 mL of acetone and magnetically stirred for 2 h. After uniform dispersion, 29.6 g of sodium hypochlorite was added and reacted at room temperature for 6 h in a dark environment. After the reaction was completed, the solvent was removed by vacuum distillation and dried in vacuo to obtain a multi-effect antibacterial agent.

[0046] Embodiment 2

[0047] Preparation of multi-effect antibacterial agent:

[0048] S1. At room temperature, under nitrogen protection, 29.4 g of isocyanuric acid was dissolved in 200 mL of deionized water in a three-necked flask equipped with a stirring device. After stirring evenly, 15.8 g of sodium hydroxide was added, and then 21.6 g of 4-chloro-1-butanol was slowly added dropwise to the three-necked flask. Under the action of magnetic stirring, the reaction was fully reacted at room temperature for 8 h. After the reaction was completed, the pH was adjusted to 6 with dilute sulfuric acid (mass fraction 12%), and the solvent was removed with a rotary evaporator. The mixture was washed with anhydrous ethanol for 3 times and dried in vacuo to obtain intermediate 1.

[0049] S2. At room temperature and under nitrogen protection, 68.6 g of phosphorus oxychloride, 27.2 g of pentaerythritol and 200 mL of anhydrous acetonitrile were mixed evenly in a three-necked flask equipped with a stirring reflux device, the reaction temperature was controlled to 65°C, the reaction was stirred for 6 hours, and then the temperature was raised to 120°C, and the reaction was refluxed until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, the solvent was distilled off under reduced pressure, the mixture was washed with dichloromethane 4 times, and vacuum dried to obtain intermediate 2;

[0050] S3, in a three-necked flask equipped with a stirring device, 84.4g of intermediate 1, 59.0g of intermediate 2, 60mL of triethylamine and 300mL of toluene were mixed and stirred uniformly, heated to 75°C, and kept warm for 3h. After the reaction was completed, triethylamine hydrochloride was filtered out, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / benzene, and the volume ratio of the two was 3:1), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 3;

[0051] S4. In a three-necked flask equipped with a stirring device, 125.2 g of intermediate 3 was mixed with 400 mL of acetone and magnetically stirred for 2 h. After uniform dispersion, 59.2 g of sodium hypochlorite was added and reacted at room temperature for 6 h in a dark environment. After the reaction was completed, the solvent was removed by vacuum distillation and dried in vacuo to obtain a multi-effect antibacterial agent.

[0052] Embodiment 3

[0053] Preparation of modified lignin:

[0054] 1 g of lignin was added to 100 mL of ethanol aqueous solution (mass fraction 42%), and after ultrasonic dispersion, 4.6 g of silane coupling agent KH-550 was added. The reaction temperature was controlled to 85 ° C. The reaction was kept warm for 5 hours with continuous stirring. After the reaction was completed, it was filtered, washed with anhydrous ethanol 3 times, and vacuum dried for 2 hours to obtain modified lignin.

[0055] Embodiment 4

[0056] Preparation of modified lignin:

[0057] 2 g of lignin was added to 200 mL of ethanol aqueous solution (mass fraction 42%), and after ultrasonic dispersion, 9.2 g of silane coupling agent KH-550 was added. The reaction temperature was controlled to 85 ° C. The reaction was kept warm for 5 hours with continuous stirring. After the reaction was completed, it was filtered, washed with anhydrous ethanol 3 times, and vacuum dried for 2 hours to obtain modified lignin.

[0058] Embodiment 5

[0059] Preparation of pre-treated PET recycled material:

[0060] 1 g of PET recycled material was added to a grinder and crushed, then added to 40 mL of water and stirred for 5 min. 3.1 g of sodium dodecylbenzene sulfonate was added and stirred for 25 min. The mixture was filtered and washed with water for 3 times. The mixture was dried in an oven at 100 °C for 2 h. The mixture was added to 20 mL of tetrahydrofuran and stirred for 30 min. The filter cake was washed with ethanol solution and dried in an oven at 100 °C for 1 h to obtain pretreated PET recycled material.

[0061] Embodiment 6

[0062] Preparation of pre-treated PET recycled material:

[0063] 2 g of PET recycled material was added to a grinder and crushed, then added to 80 mL of water, stirred for 5 min, 6.2 g of sodium dodecylbenzene sulfonate was added, stirring was continued for 25 min, filtered, washed with water 3 times, dried in an oven at 100 ° C for 2 h, added to 40 mL of tetrahydrofuran, stirred for 30 min, filtered, the filter cake was washed with ethanol solution, and dried in an oven at 100 ° C for 1 h to obtain pretreated PET recycled material.

[0064] Embodiment 7

[0065] 80 g of the pretreated PET recycled material prepared in Example 5, 10 g of the modified lignin prepared in Example 3, 6 g of the multi-effect antibacterial agent prepared in Example 1, 4 g of antioxidant 1010 and 3 g of stearic acid were stirred and mixed evenly in a mixer, and then put into a twin-screw extruder, melt blended, extruded and granulated to obtain a plastic masterbatch based on recycled PET materials.

[0066] Embodiment 8

[0067] 90 g of the pretreated PET recycled material prepared in Example 5, 15 g of the modified lignin prepared in Example 3, 12 g of the multi-effect antibacterial agent prepared in Example 1, 6 g of antioxidant 1010 and 4 g of zinc stearate were stirred and mixed evenly in a mixer, and then put into a twin-screw extruder, melt blended, extruded and granulated to obtain a plastic masterbatch based on recycled PET materials.

[0068] Embodiment 9

[0069] 100 g of the pretreated PET recycled material prepared in Example 5, 20 g of the modified lignin prepared in Example 3, 18 g of the multi-effect antibacterial agent prepared in Example 1, 8 g of antioxidant 1010 and 5 g of magnesium stearate were stirred and mixed evenly in a mixer, and then put into a twin-screw extruder, melt blended, extruded and granulated to obtain a plastic masterbatch based on recycled PET materials.

[0070] Comparative Example 1

[0071] The multi-effect antibacterial agent in Example 9 was replaced by a commercially available antibacterial agent of equal quality, and the remaining steps were the same as those in Example 9 to obtain a masterbatch.

[0072] Comparative Example 2

[0073] The multi-effect antibacterial agent in Example 9 was replaced by a commercially available phosphorus-based flame retardant of equal quality, and the remaining steps were the same as those in Example 9 to obtain a masterbatch.

[0074] Comparative Example 3

[0075] Commercially available recycled PET masterbatch was used.

[0076] Embodiments 7, 8, 9 and comparative examples 1, 2, 3 were made into corresponding shapes according to different test standards and the following performance tests were performed:

[0077] The tensile strength was determined using the national standard GB / T 1040-2006 "Determination of tensile properties of plastics";

[0078] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to determine the limiting oxygen index;

[0079] The antibacterial rate of Staphylococcus aureus and Escherichia coli in the sample was determined using QB / T 2591-2003A "Test methods and antibacterial effects of antibacterial plastics";

[0080] The measured results are shown in the following table:

[0081]

[0082] It can be seen from the above table that the masterbatch prepared in the embodiment of the present invention has good mechanical properties, and its antibacterial and flame retardant properties are higher than those of the control example, and has important application value in the field of plastic recycling technology.

[0083] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0084] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing plastic masterbatch based on recycled PET materials, characterized in that: The following steps are involved: The pretreated PET recycled material, modified lignin, multi-effect antibacterial agent, antioxidant and lubricant are stirred and mixed evenly in a mixer, and then put into a twin-screw extruder for melt blending, extrusion and granulation to obtain a plastic masterbatch based on recycled PET material.

2. The method for preparing a plastic masterbatch based on recycled PET materials according to claim 1, characterized in that: The multi-effect antibacterial agent is prepared by the following steps: S1. Dissolve isocyanuric acid in deionized water at room temperature under nitrogen protection, add sodium hydroxide after stirring evenly, and then slowly drop 4-chloro-1-butanol into a three-necked flask. Under magnetic stirring, fully react at room temperature for 8 hours. After the reaction is completed, adjust the pH to 6-7, remove the solvent with a rotary evaporator, wash, and vacuum dry to obtain intermediate 1; S2. At room temperature and under nitrogen protection, phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile were mixed evenly, reacted at 65°C for 6 hours, and then the temperature was raised to 120°C, and refluxed until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, washed, and dried to obtain intermediate 2; S3, mixing intermediate 1, intermediate 2, triethylamine and toluene, and heating to 75°C, and keeping the temperature to react for 3 hours. After the reaction is completed, filtering, rotary evaporation, column chromatography purification, rotary evaporation, and drying to obtain intermediate 3; S4. Mix the intermediate 3 with acetone, stir magnetically for 2 hours, add sodium hypochlorite after it is evenly dispersed, and react at room temperature for 6 hours in a dark environment. After the reaction is completed, perform vacuum distillation and vacuum drying to obtain a multi-effect antibacterial agent.

3. A method for preparing plastic masterbatch based on recycled PET materials according to claim 2, characterized in that: In step S1, the ratio of isocyanuric acid, deionized water, sodium hydroxide and 4-chloro-1-butanol is 14.7 g: 100 mL: 7.9 g: 10.8 g.

4. The method for preparing a plastic masterbatch based on recycled PET materials according to claim 2, characterized in that: In step S2, the ratio of phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile is 34.3 g:13.6 g:100 mL.

5. The method for preparing a plastic masterbatch based on recycled PET materials according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 1, intermediate 2, triethylamine and toluene is 42.2 g:29.5 g:30 mL:150 mL.

6. A method for preparing plastic masterbatch based on recycled PET materials according to claim 2, characterized in that: In step S4, the ratio of the amount of intermediate 3, acetone and sodium hypochlorite is 62.6 g:200 mL:29.

6.

7. The method for preparing plastic masterbatch based on recycled PET materials according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 80-100 parts of pre-treated PET recycled material, 10-20 parts of modified lignin, 6-18 parts of multi-effect antibacterial agent, 4-8 parts of antioxidant, and 3-5 parts of lubricant.

8. The method for preparing plastic masterbatch based on recycled PET materials according to claim 1, characterized in that: The modified lignin is prepared by the following steps: Add lignin to ethanol aqueous solution, disperse it evenly by ultrasonication, then add silane coupling agent KH-550, control the reaction temperature to 85°C, keep the reaction for 5 hours, stir continuously during the reaction, filter, wash with anhydrous ethanol 2-3 times, and vacuum dry for 2 hours to obtain modified lignin.

9. A method for preparing plastic masterbatch based on recycled PET materials according to claim 8, characterized in that: The usage ratio of the lignin, the ethanol aqueous solution and the silane coupling agent KH-550 is 1 g:100 mL:4.6 g.

10. A plastic masterbatch based on recycled PET materials, characterized in that: Prepared according to the method according to any one of claims 1 to 9.